WOx/ZrOx functionalised periodic mesoporous organosilicas as water-tolerant catalysts for carboxylic acid esterification. Issue 7 (2nd March 2023) - dos Santos-Durndell, Vannia C.; Durndell, Lee J.; Isaacs, Mark A.; Lee, Adam F.; Wilson, Karen
Abstract : Kicking out water: optimising the interaction between support hydrophobicity and surface acid sites in WO x /ZrO x /PMO catalysts unlocks an efficient route for the upgrading of low-quality waste bio-oil feedstocks to biodiesel. Abstract : Catalyst hydrophobicity is an oft-neglected property despite its significance in aqueous phase reactions and those wherein water is a by-product, such as condensation and esterification. Here we synthesise WO x /ZrO x impregnated periodic mesoporous organosilicas (PMOs) of varying organic framework content, through the stepwise substitution of bis(triethoxysilyl)benzene (BTSB) for tetraethyl orthosilicate (TEOS), followed by tungsten and zirconium co-grafting. Incorporation of phenyl groups into the framework of mesoporous SBA-15 silica imparts surface hydrophobicity and tunes the solid acidity, while preserving the textural properties of the parent silica. The resulting WO x /ZrO x /PMO catalysts exhibit excellent turnover frequencies (TOFs) for the esterification of C3 –C16 carboxylic acids in methanol at 60 °C, with TOFs inversely proportional to fatty acid chain length. The superior activity and stability (water tolerance up to 50 mol%) of WO x /ZrO x /PMO versus WO x /ZrO x /SBA-15 is attributed to the displacement of water from in-pore active sites, mitigating the reverse ester hydrolysis reaction. Such hydrophobic, solid acid catalysts are anticipated to find widespread application in aqueous phase synthesis, particularly of biorefinery output streams.